Implementation of Bureaucratic Simplification Policy in the Regional Government of Tangerang Regency - Rizky Agustian Mubarok; Deddy S. Bratakusumah; Agung Edi Rustanto; Ahmad Hidayat Sutawidjaya (International Publisher (YAPENBI), 2024)
Indonesian bureaucracy since the beginning of the reform era has shown little progress because there are still many arrogant bureaucrats who practice corruption, collusion, nepotism, and waste as well as many abuses of government authority and power for personal gain at all levels and systems of government. With the various dynamics that occur, several strategies are carried out by the government for bureaucratic reform by implementing a merit system policy, forming an ethics committee board and encouraging transparency in publication or open complaints against any violation of regulations to issuing bureaucratic reform regulations and institutional transformation. The bureaucratic reform policy in Indonesia is carried out through bureaucratic simplification by transferring administrative positions to functional positions and forming a new work system. This study uses a qualitative descriptive research approach, using data triangulation techniques involving the use of various data sources to examine the same phenomenon, including interview data, observations, and supporting documents. The results of this study indicate that the implementation of the bureaucratic simplification policy in the Tangerang Regency Government has provided quite significant changes and in a positive direction. The implementation of the bureaucratic simplification policy has changed the organizational structure of regional apparatus by eliminating one level of organizational structure. Overall, this study concludes that the simplification of bureaucracy in the Tangerang Regency Government has gone well in terms of administration. However, further evaluation and monitoring are still needed to ensure the efficiency and effectiveness of this policy in accordance with applicable laws and regulations, especially in the aspects of work culture for communication changes, education and training for increasing resources, disposition to the new work system and the running of the bureaucratic structure after bureaucratic simplification.